KARDIOCHIRURGIA DOROSŁYCHTransmyocardial laser revascularization (TMLR) – a safe alternative for patients with “no option” coronary artery disease - Śliwiński, Marian; Juraszyński, Zbigniew; Dyk, Wojciech; Wojno, Anna; Szymańska, Maria; Biederman, Andrzej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Aim: The goal of the study was to evaluate early complications in patients with “no option” coronary heart disease subjected to lone transmyocardial laser revascularization (TMLR), or TMLR with coronary artery bypass grafting (CABG). Material and methods: 150 consecutive patients with “no option” coronary artery disease (CAD) were operated on between January 2004 and November 2008. There were 45 female and 105 male patients aged 42 to 81 years, mean age 65.5 years. 35 pts underwent lone TMLR procedure, and 115 pts underwent TMLR + CABG. All patients were monitored for: need for inotropic support, troponin release, myocardial ischaemia or MI, heart rhythm disturbances, bleeding or septic complications. Results: 6 pts (4%) needed support with dobutamine and IABP; 3 pts (2%) needed support with dobutamine, epinephrine and IABP; 33 pts (22%) had increased level of troponin above 10; 9 pts (5.9%) had diagnosis of new myocardial infarction; 13 pts (8.6%) had ventricular arrhythmia, 4 pts with VF required defibrillation. Other complications were rare and transient and included: re-thoracotomy for bleeding in 4 patients; neurological deficit, infection and asystole in 1 patient each. One patient died on the second postoperative day, because of intraoperative myocardial infarction. Conclusions: TMLR as a lone procedure, or combined with CABG, is a safe procedure with low mortality and minor transient complications. This procedure can be recommended for patients with “no option” CAD.